Gallium-Based Room-Temperature Liquid Metals: Actuation and Manipulation of Droplets and Flows - Majidi, Leily; Gritsenko, Dmitry; Xu, Jie (Frontiers in Mechanical Engineering, 2017)
Gallium based room-temperature liquid metals possess extremely valuable properties, such as low toxicity, low vapor pressure, and high thermal and electrical conductivity enabling them to become suitable substitutes for mercury and beyond in wide range of applications. When exposed to air, a native oxide layer forms on the surface of gallium based liquid metals which mechanically stabilizes the liquid. By removing or reconstructing the oxide skin shape and state of liquid metal droplets and flows can be manipulated/actuated desirably. This can occur manually or in the presence/absence of a magnetic/electric field. These methods lead to numerous useful applications such as soft electronics, reconfigurable devices and soft robots. In this mini-review, we summarize the most recent progresses achieved on liquid metal droplet generation and actuation of gallium based liquid metals with/without an external force.